Reproductive success of the South American Tern, Sterna hirundinacea Lesson, 1831 (Aves: Laridae), at an artificial site in the coast of São Paulo state, Brazil - Léo C. M. Fonseca; Edison Barbieri (Ocean and Coastal Research)
Sterna hirundinacea, a seabird species, has been extensively studied in natural habitats; however, information on its reproduction in artificial environments is still limited. This study investigates the nesting behavior and reproductive success of S. hirundinacea at the Terminal Aquaviário da Petrobrás (TEBAR), an artificial site located on the north coast of São Paulo state, Brazil. From April to September 2021, 57 nests were selected for monitoring at 48-72-hour intervals from a total of 159 nests and 318 mature individuals reproducing within the colony. The breeding season lasted 145 days, with an average clutch size of 1.21 ± 0.41 eggs per nest, including single-egg nests (n = 45) and double-egg nests (n = 12). Nine instances of egg replacement were recorded. A total of 78 eggs were laid, with a mean length of 4.56 ± 0.22 cm, a mean width of 3.26 ± 0.09 cm, and a mean volume of 25.45 ± 2.01 cm³. The study documented a mean egg mass reduction of 0.39 ± 0.02 g per interval. Egg losses (n = 63) were attributed to predation (60.3%), inviability (34.9%), and stillbirth (4.8%). The mean incubation period was 23.73 ± 2.34 days. Of the remaining 15 healthy fledglings, 11 (73.3%) did not survive; causes of mortality included predation or falls into the sea (54.5%), collisions (36.4%), and natural causes (9.1%). Mortality peaked during the first nine days after hatching, further increasing at 21-30 days of age. Only four fledglings made it to flight, resulting in a reproductive success rate of 5.1%. TEBAR showed both similarities and differences in S. hirundinacea reproduction at the artificial site compared with natural nesting sites. Human activities at the site likely contributed to higher egg and fledgling losses due to predation and disturbance. Regular monitoring and further research are essential to assess the impact on S. hirundinacea and to develop conservation strategies if necessary.